Contributing to a National Early Learning and Child Care System in Canada: An Environmental Scan of Early Childhood Policy and Programs - Gorica, Yalin; Jalali-Kushki, Yasaman; Wang, Mei; Conforzi, Jennifer (SOURCE: Sheridan Institutional Repository, 2023)
As the federal government aims to establish a Canada-wide Early Learning and Child Care system with all provinces and territories, the significance of having a trained and qualified early childhood education (ECE) workforce is paramount to ensuring the provision of high-quality child care services to children. The shortage of qualified early learning and child care staff across the country calls for more research and program development to understand the complex issues of recruiting, supporting, and retaining qualified ECE professionals in the field. This environmental scan presents an opportunity for researchers to conduct a comprehensive review of current research trends and practices in early learning and child care and to explore the diverse needs of the community, as well as the ability of the child care sector to support children and families. The methods used in this environmental scan include a literature review of relevant studies and reports published in the last 5-10 years. It encompasses a wide range of academic research articles pertinent to early childhood issues and practices, as well as governmental documents and reports from local, provincial, and federal governments or governmental agencies. Additionally, documents and reports published by organizations in the child care sector, advocacy groups, labour unions, and those related to First Nations perspectives in child care and early learning system were examined. Through a comprehensive assessment of early childhood policies and programs, this environmental scan focuses on four key aspects: 1) early childhood education policies in Canada, 2) community needs and childcare, 3) early childhood practices and training, and 4) the quality of early childhood programs. By analyzing the factors that shape the ECE environment and their impact on children, families, and educators, it provides a better understanding of the challenges and opportunities within the field. This broader examination enables the identification of areas for further research, ...